Halal Halal Literacy Profile of Class VIII Students Through Science Learning on The Subject of The Human Digestive System at SMP Edu Global School Bandung - Kulsum, Fitriani; Rohman, Chaerul (Islamic Research, 2025)
Education is the process of changing someone from being unable to being able to, from not knowing to knowing. In the implementation of education there is a curriculum in order to realize educational goals. The current curriculum applies in accordance with the times, namely in the era of the 21st century. One of the curriculums in the 21st century is that students must be able to master literacy and global competition. Global competition, namely in the economic realm regarding halal. In relation to learning, the teacher must be able to integrate literacy skills with halal. Learning in schools integrates learning design with halal literacy. This study aims to determine the initial ability of halal literacy in students through science learning. The method in this study uses quantitative research methods by providing questions related to four aspects of halal literacy, namely the concept of halal and natural science, halal process, halal benefits, and attitudes. The subject of this research was class VIII students as many as 26 respondents. The results of this study show that the average percentage of halal concept aspects and IPA is 37.5%, the average percentage of halal process aspects is 45.2%, the average percentage of halal benefit aspects is 60.6%, and the average percentage of attitude aspects 39.4%. The average percentage of students' halal literacy ability is 55,05%. The results of this study can be used as a basis for research related to increasing students' halal literacy.